Eosinophilic Fasciitis Associated with Myositis - Yuko Adachi; Yoko Mizutani; En Shu; Hiroyuki Kanoh; Tatsuhiko Miyazaki; Mariko Seishima (Karger Publishers, 2015)
Eosinophilic fasciitis is clinically characterized by symmetrical scleroderma-like indurations of the skin with pain. The histological features are fascial inflammation with lymphocytes and eosinophils as well as thickened and fibrotic fascia. Lymphocytic infiltration and degeneration of the underlying muscle are rarely observed. We report a 69-year-old Japanese woman who presented with multiple areas of glossy induration and painful peau d'orange-like lesions on the chest and four extremities. T2-weighted magnetic resonance imaging showed significant hyperintense thickening of the fascia of the lower extremities. Histopathological examination of a biopsy specimen from the induration showed marked fibrinoid degeneration of the fascia and the neighboring muscle with mixed cellular infiltration of lymphocytes and eosinophils. The predominant CD8+ lymphocytic infiltrates were observed by immunohistological study. A diagnosis of eosinophilic fasciitis with myositis was made. Oral administration of prednisolone and discontinuation of exercise significantly improved the lesions and pain.